Improving Students Critical Thinking Skills and Sustainability Awareness using Problem Based Learning Model - Maulina*, Dina; Priadi, Median Agus; Gustina, Melin; Rakhmawati, Ismi (Jurnal Pendidikan Sains Indonesia, 2025)
This research aims to determine the increase in students' critical thinking skills (CTS) and sustainability awareness in SDGs issue-oriented climate change material using a problem-based learning (PBL) model. This type of research is quantitative research, the research design is quasi-experimental with a pretest-posttest non-equivalent control group design technique. The research sample consisted of two classes selected using purposive sampling technique. Research data was obtained by providing a pretest and posttest to determine the increase in CTS and an observation sheet to determine students' sustainability awareness data. The pretest-posttest scores in the experimental class using the PBL model obtained an average N-gain score of 0.52, including the medium category. The effect size test also obtained a value of 2.88 with the "large" criterion. The results of the sustainability awareness questionnaire data obtained an average percentage of 81.42% with a frequency of "often or always done". Based on these data, it can be concluded that the PBL model has a significant effect on improving CTS and influences sustainability awareness in climate change material that is oriented to SDGs issues. The use of PBL models can be an effective strategy in improving CTS and instilling sustainability awareness